The 'answer' is the number that ' c ' must be in order to make the statement true.
In this case, there are two of them that will both work.
c2 + 10c + 24 = 0
(c + 6) (c + 4) = 0
c + 6 = 0 ===> c = -6
c + 4 = 0 ===> c = -4
original problem: c2-10c+24=0 reverse foil: (c-6)(c-4)=0 so... c-6=0 OR c-4=0 +6 +6 +4 +4 c=6 OR c=4
l a2 b2 is c2!!Its completely norma
52+32 = c2 34 = c2 c = the square root of 34
a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z
12c
original problem: c2-10c+24=0 reverse foil: (c-6)(c-4)=0 so... c-6=0 OR c-4=0 +6 +6 +4 +4 c=6 OR c=4
a2
l a2 b2 is c2!!Its completely norma
Pythagorean Theorem
a right triangle
52+32 = c2 34 = c2 c = the square root of 34
a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z
12c
You just typed it.
* a2 + b2 = c2 * a = 3 * b = 8 * (3)2 + (8)2 = c2 * 9 + 64 = c2 * 73 = c2 * c = √73
c= -2 2/7 OR -2.285714
a2+b2 = c2 92+52 = c2 81+25 = c2 106 = c2 Square root both sides to find the value of c: c = the square root of 106 => 10.29563014